1995
DOI: 10.1111/j.1525-1594.1995.tb02368.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Idiotypic and Antiidiotypic Immunoglobulin G Responses in an Immune Thrombocytopenic Purpura Patient as a Consequence of Extracorporeal Protein A Immunoadsorption

Abstract: Immune thrombocytopenic purpura (ITP) is an autoimmune disorder characterized by the presence of antiplatelet antibody which sensitizes platelets resulting in their clearance by the reticuloendothelial system. Extracorporeal protein A immunoadsorption has been demonstrated to be of benefit in the treatment of this autoimmune disorder. In the present study, a patient with underlying systemic lupus erythematosus (SLE) presented with ITP. The patient received 14 immunoadsorption treatments and responded to therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…From our results we propose to consider the lack of C3a inactivation in a similar way as with the suggested lack of bradykinin degrading enzymes in certain patients, as we propose that in addition to removal and/or modulation of immune complexes, complement activation was a second major reaction that was taking place during Prosorba ® therapy. Complement activation can lead to recruitment and activation of leukocytes and platelets, resulting in an intense inflammatory cascade 33–35, 43. It is known that cleavage of the C‐terminal arginine residue of bradykinin, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our results we propose to consider the lack of C3a inactivation in a similar way as with the suggested lack of bradykinin degrading enzymes in certain patients, as we propose that in addition to removal and/or modulation of immune complexes, complement activation was a second major reaction that was taking place during Prosorba ® therapy. Complement activation can lead to recruitment and activation of leukocytes and platelets, resulting in an intense inflammatory cascade 33–35, 43. It is known that cleavage of the C‐terminal arginine residue of bradykinin, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These circulating particles were thought to possibly combine with circulating IgG, either free or antigen‐complexed, to form protein A‐induced circulating immune complexes. In this context it had been speculated that removal of immune complexes may have abrogated important negative feedback mechanisms on pathogenic B‐cell clones leading to increased production of free undesired antibodies, thereby potentially leading to a worsening of disease 32, 33, 43. Although we do not rule out the occurrence of such protein A‐related side reactions during Prosorba ® therapy in patients completely, we assume that C3a release into the patient́s circulation may be sufficient in explaining the adverse events mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…SPA columns have increasingly been used in the treatment of a number of refractory autoimmune disorders, including RA and ITP. SPA binds with greater affinity to the Fc portion of IgG complexed to antigen than to the Fc portion of free uncomplexed IgG [6]. Thus, the efficacy of plasma immunoadsorption with SPA in the treatment of autoimmune disease may be attributable in part to the removal of pathogenic circulating immune complexes containing IgG [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Perfusion of plasma through SPA columns results in neutrophil activation, complement activation, and increased T-helper-cell activity [4,6,9,[10][11][12][13][14]. Complement activation can lead to recruitment and activation of leucocytes and platelets, resulting in an intense inflammatory cascade [6,[9][10][11]. Moreover, studies have shown that minute quantities of soluble SPA-silica can leach out of the SPA column, yielding plasma concentrations from 0.23 to 70 mcg/ml [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation